2010
DOI: 10.1002/mus.21683
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and verification of amyotrophic lateral sclerosis biomarkers by proteomics

Abstract: Introduction Recent studies using mass spectrometry have discovered candidate biomarkers for amyotrophic lateral sclerosis (ALS). However these studies utilize small numbers of ALS and control subjects. Additional studies using larger subject cohorts are required to verify these candidate biomarkers. Methods Cerebrospinal fluid (CSF) from 100 patients with ALS, 100 disease control and 41 healthy control subjects were examined by mass spectrometry. Results 61 mass spectral peaks exhibited altered levels bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
83
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 40 publications
11
83
1
1
Order By: Relevance
“…Immobilization, disuse or denervation triggers muscular atrophy, which clearly shows that neuromuscular innervation patterns are directly linked to gene expression, protein abundance and isoform patterns in skeletal muscles [29]. In analogy to the recent proteomic profiling of cerebrospinal fluids from patients suffering from ALS and the spinal cord from the wobbler mouse [19][20][21][22][23], this study describes the findings of the MS-based proteomic survey of skeletal muscle from the WR mouse. From the detailed analysis of the isoform patterns of the sarcomeric MyHCs it became clear that the response of gene expression in skeletal muscle to denervation is characteristically different from that to hyper-excitability and muscular dystrophy [28].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Immobilization, disuse or denervation triggers muscular atrophy, which clearly shows that neuromuscular innervation patterns are directly linked to gene expression, protein abundance and isoform patterns in skeletal muscles [29]. In analogy to the recent proteomic profiling of cerebrospinal fluids from patients suffering from ALS and the spinal cord from the wobbler mouse [19][20][21][22][23], this study describes the findings of the MS-based proteomic survey of skeletal muscle from the WR mouse. From the detailed analysis of the isoform patterns of the sarcomeric MyHCs it became clear that the response of gene expression in skeletal muscle to denervation is characteristically different from that to hyper-excitability and muscular dystrophy [28].…”
Section: Resultsmentioning
confidence: 97%
“…The current international effort to discover reliable biomarkers of ALS [16] includes the verification of both suitable metabolites [17] and protein factors [18]. Recent proteomic profiling studies of ALS patient samples and the WR animal model have focused on the analysis of cerebrospinal fluid [19][20][21] and cervical and lumbar spinal cord [22,23], respectively. The studies on the WR mouse showed that the majority of differentially expressed proteins were related to the glutamate-glutamine cycle, energy transduction, redox functions and astrogliosis [22], thus confirming previous studies [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts in our group, as well as others, identified cystatin C as a potential biomarker in the CSF of patients with ALS [49,[97][98][99][100]. Cystatin C is a cysteine protease inhibitor that is involved in extracellular matrix (ECM) regulation, as well as a variety of CNS diseases [101,102].…”
Section: Cystatin Cmentioning
confidence: 98%
“…Using surfaceenhanced laser desorption/ionization, reduced levels of cystatin C were observed in CSF from patients with ALS as compared with control subjects (healthy and diseased) [97]. Levels of cystatin C positively correlated with survival time for patients with limb onset but did not correlate with the disease duration [98]. A longitudinal study was also performed on CSF and plasma over a 1 to 2-year time period [105].…”
Section: Cystatin Cmentioning
confidence: 99%
“…These differences can be used to develop biomarkers of disease and provide insights into disease pathogenesis. Feasibility of a proteomics approach as well as disease-relevant changes have been described in both plasma (12)(13)(14) and cerebrospinal fluid (15)(16)(17), highlighting the utility of proteomics in biomarker development. We, and others, have also demonstrated the potential for this approach in identifying neurodegenerative-specific changes in postmortem brain tissues.…”
mentioning
confidence: 99%